Interfacing nanocarbons with organic and inorganic semiconductors from nanocrystals/quantum dots to extended tetrathiafulvalenes - Katsukis, Georgios (Langmuir : the ACS journal of surfaces and colloids, 2012)
There is no doubt that the outstanding optical and electronic properties that low-dimensional carbon-based nanomaterials exhibit call for their implementation into optoelectronic devices. However, to harvest the enormous potential of these nanocarbons it is essential to probe them in multifunctional electron donor-acceptor systems, placing particular attention on the interactions between electron donors/electron acceptors and nanocarbons. This feature article outlines challenges and recent breakthroughs in the area of interfacing organic and inorganic semiconductors with low-dimensional nanocarbons that range from fullerenes (0D) and carbon nanotubes (1D) to graphene (2D). In the context of organic semiconductors, we focus on aromatic macrocycles and extended tetrathiafulvalenes, and CdTe nanocrystals/quantum dots represent the inorganic semiconductors. Particular emphasis is placed on designing and probing solar energy conversion nanohybrids